A New Approach for Exiting from Parking Lot based on Artificial Neural Network - Ozturk, Halil; Teke, Sevginur; Karabatak, Murat (Ieee, 2019)
With developing technology, autonomous vehicle systems have become very important. One of the biggest problems of these vehicles is entering to parking lots and exiting from parking lots. As well as parallel parking and vertical parking problems, exiting from a parking lot can also be a problem in some cases. In this paper, it is aimed to find a solution to the problem of exiting the vehicles from the parking lot. Due to the location and structure of the parking lots, it can be difficult to exit from a parking lot for a vehicle. In this study, data such as speed, wheel angle and position of the vehicle were obtained from the vehicle and it is aimed to automatically exit from the parking lot. Artificial Neural Network was used to perform this procedure. The modeling results show that it is possible for a vehicle to exit autonomously from the parking lot.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Artificial Neural Network; Time Series Analysis; Parking Problem; Vehicle